THE INTERACTION OF Ag-CONTAINING PORPHYRINS WITH DNA AT HIGH IONIC STRENGTH - Sulyman, S. A. A.; Ghazaryan, A. A.; Dalyan, Ye. B. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2009)
UV-VIS spectrophotometry and circular dichroism (CD) methods were applied to study the binding of DNA with three novel Ag-containing porphyrins meso-tetra(4N-allylpyridyl) (AgTAlPyP4), meso-tetra(4N-butylpyridyl) (AgTButPyP4) and meso-tetra(4N-oxyethylpyridyl) (AgTOEtPyP4) at high ionic strength. The binding constant Kb and stoichiometry n were determined from binding isotherms for each ligand–DNA complex. The Gibbs free energy, enthalpy and entropy of binding also were calculated using the values of Kb . Obtained results show that these porphyrins associate with the duplex DNA via outside binding mode.
Keywords: DNA; porphyrin; ionic strength